Taxonomic and ecological data on the Hemiptera fauna from Berati region habitats in Albania - Eltjon Halimi; Anila Paparisto; Era Alameti (Journal of Biological Research, 2023)
This study provides taxonomic and ecological data on Hemiptera (Insecta) order prevalence in Berati region habitats in Southern Albania. Diverse natural environments, fields, and hilly and mountainous habitats characterize this region. The expeditions for the biological material collection were organized during 2018-2020 in six stations from May to September. Our study refers to 38 species, representing 28 genera and 10 families of the order Hemiptera. Taxonomical results on the family distribution indicate that the highest belonged to Pentatomidae, with 12 species or 31.5%, followed by Miridae, with 9 species and 23.6%. Regarding species diversity, the Lybesha station had the highest diversity, with 16 species or 41.1%, while the Lapardha station had the lowest diversity, with six species or 15.7%. Estimating species similarity by the Jaccard coefficient indicates the Lybesha and Peshtani stations, with four common species and a species similarity coefficient of 16.6%, reflecting the ecological factors' similarity between these stations.